The impact of non-residential grandchild care on physical activity and sedentary behavior in people aged 50 years and over: study protocol of the Healthy Grandparenting Project - Marie Vermote; Tom Deliens; Benedicte Deforche; Eva D'Hondt (BMC, 2021)
Abstract Background Finding effective ways to support people aged > 50 years to develop adequate levels of physical activity and sedentary behavior is necessary as these behaviors are positively related to the maintenance of functional independence and health-related quality of life. Given the widespread provision of grandparental child care, examining its impact on grandparents' energy-expenditure related behavior in the broader context of health is imperative. Therefore, the Healthy Grandparenting Project will aim to investigate the levels of physical activity and sedentary behavior, body composition and health-related quality of life in grandparents caring for their grandchildren and to compare these outcomes with non-caregiving grandparents and older adults without grandchildren, both momentarily and over time. An additional purpose is to identify possible predictors of potential changes over time. Methods A prospective cohort study will run over a period of 2 years, including three test occasions with a one-year time interval in between (T0 = baseline, T1 = 12 months, T2 = 24 months). A total of 276 participants will be recruited in Flanders through non-probability quota sampling (50-50% men-women), of which 92 caregiving grandparents, 92 non-caregiving grandparents and 92 non-grandparents. All three subsamples will be matched for age and sex. At each test occasion, anthropometric and body composition measurements will be determined. Participants' levels of physical activity and sedentary behavior will be assessed both objectively and subjectively by means of accelerometry and self-report questionnaires. Information about their grandchildren and the provided grandparental care (if applicable) as well as their health-related quality of life will also be assessed using self-report questionnaires. Mixed modelling will be used to identify differences in physical activity, sedentary behavior, body composition and health-related quality of life between the subsamples at baseline, as well as to evaluate and compare changes in energy-expenditure related behavior over time between subsamples and to identify predictors of the detected changes. Discussion The Healthy Grandparenting Project is an innovative study examining the levels of physical activity and sedentary behavior in caregiving grandparents, non-caregiving grandparents and non-grandparents. Obtained results will help in the development of campaigns to maintain/improve health in adults at a more advanced age. Trial registration clinicaltrials.gov, Identifier: NTC04307589 . Registered March 2020.